1993
DOI: 10.1111/j.1526-4610.1993.hed3303145.x
|View full text |Cite
|
Sign up to set email alerts
|

An Association Between Migrainous Aura and Hereditary Haemorrhagic Telangiectasia

Abstract: Hereditary haemorrhagic telangiectasia (HHT) is a rare autosomal dominant disorder characterized by a variety of abnormalities of the vasculature. This study investigated by questionnaire an unselected group of 58 patients suffering from HHT to identify and diagnose any headache history. These were compared with a control group comprising 40 patients with an unrelated autosomal dominant disorder, familial adenomatous polyposis. Fifty percent of the HHT patients reported attacks of headache which fulfilled curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 0 publications
0
42
1
1
Order By: Relevance
“…12,40,50,[52][53][54] Others have noted a high occurrence of cases of migraine headaches in patients with HHT and pulmonary AVFs. 55 It remains unsettled whether this frequent finding represents an increase over the normal incidence of migraine headaches in the population. 56 Our data confirm the high risk of cerebral ischemic complications and abscesses in patients with HHT that is related to pulmonary AVFs.…”
Section: Discussionmentioning
confidence: 99%
“…12,40,50,[52][53][54] Others have noted a high occurrence of cases of migraine headaches in patients with HHT and pulmonary AVFs. 55 It remains unsettled whether this frequent finding represents an increase over the normal incidence of migraine headaches in the population. 56 Our data confirm the high risk of cerebral ischemic complications and abscesses in patients with HHT that is related to pulmonary AVFs.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by STEELE et al [31], it is suggested that CAVM might play a role in the pathogenesis of migraine in HHT patients. In the present study, we found no association between the presence of a CAVM and overall prevalence of no migraine or MA.…”
Section: Discussionmentioning
confidence: 99%
“…As many as 71% of patients with PAVMs secondary to HHT experience headache symptoms and y55% satisfy criteria for the diagnosis of migraine [3]. Though frequency of headache is unknown for patients with sporadic PAVMs, the presentation of the patient with headache, which resolved after PAVM embolization, suggests that the aetiology of her headache was related to the PAVM.…”
Section: Discussionmentioning
confidence: 94%